Congenital heart block and immune mediated sensorineural hearing loss: possible cross reactivity of immune response. (July 2017) - Bason, C; Pagnini, I; Brucato, A; Maestroni, S; Puccetti, A; Lunardi, C; Cimaz, R
Immune-mediated sensorineural hearing loss may complicate systemic autoimmune diseases. We have previously reported the presence of antibodies directed against inner ear antigens in patients with Cogan syndrome, a disease characterized by sudden hearing loss and interstitial keratitis. Such autoantibodies cross-react with an epitope of SSA/Ro60 protein. Anti-Ro/SSA antibodies in pregnant women cross the placenta and reach the fetal tissues inducing an immune-mediated damage of the cardiac conduction system. We wanted to evaluate whether mothers with anti-Ro/SSA antibodies who gave birth to children with congenital heart block have antibodies directed against inner ear antigens and whether these antibodies are connected with the presence of immune-mediated sensorineural hearing loss. We did not find anti-inner ear antibodies in the majority of the mothers. On the contrary a 13-year-old boy with congenital heart block and sensorineural hearing loss was positive for the presence of anti-inner ear antigens antibodies. Moreover his serum was positive for the presence of anti-Ro60 peptide antibodies but did not recognize the entire protein Ro60 (TROVE2), a behaviour similar to that of sera from patients with Cogan syndrome. In conclusion the data obtained so far show that anti-inner ear antibodies do not recognize the entire protein TROVE2 and do not support the hypothesis that such antibodies may be involved in the pathogenesis of congenital heart block.